Fundamentals of Co-Evolution Development - Mihnev, Georgi (Research Papers, 2012)
There are many debates within the scientific community regarding the problem of so called “sustainable development”. Some reject the concept of sustainable development, while others think all governments should follow certain principles in order to prevent an ecological disaster.The definition of sustainable development formulated by United Nations World Commission on Environment and Development in their 1987 report called “Our Common Future” also known as the Brundtland Report says that Sustainable development (SD) is a pattern of resource use, thataims to meet human needs while preserving the environment so that these needs can be met notonly in the present, but also for generations to come. The very definition of SD gives some ground for the skeptics. Needs of generations and technologies to meet these needs change dramatically from generation to generation, and it is impossible to predict which of the resources we use today should be preserved for future generations. Another major drawback is that it SD requires constant economical growth which was never achieved by any society, neither in socialist nor capitalist economy. Development is rather associated with crises that are being overcomed by organizational and structural changes involving innovative methods of the production of goods and services.In this study we have used the systemic approach. It was used for the first time by Russian scientists Vernadsky, Bogdanov and Buharin. Vernadsky introduces the term “noosphere”. In the original theory of Vernadsky, the noosphere is the third in a succession of phases of development of the Earth, after the geosphere (inanimate matter) and the biosphere (biological life). Just as the emergence of life fundamentally transformed the geosphere, the emergence of human cognition fundamentally transforms the biosphere.We think instead of “sustainable development” should be considered the term “co-evolution development”, which leads to a balanced interaction of man and nature. Such kind of development could be achieved by elaboration of goods and services production but also by improving the ethics and morality of people.The Noospere research is a dynamic process of learning and assessment of the interactions of it’s elements. Our attention should be concentrated on the indicators describing the state of its major subsystems, and also on deepening the knowledge of the risks which carry one or another development project.